2012
DOI: 10.4236/ajmb.2012.21001
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of haptoglobin with hemoglobin octamers based on the mutation <i>α</i>Asn78Cys or <i>β</i>Gly83Cys

Abstract: Octameric hemoglobins have been developed by the introduction of surface cysteines in either the alpha or beta chain. Originally designed as a blood substitute, we report here the structure and ligand binding function; in addition the interaction with haptoglobin was studied. The recombinant Hbs (rHbs) with mutations alpha Asn78Cys or beta Gly83Cys spontaneously form octamers under conditions where the cysteines are oxidized. Oxygen binding curves and CO kinetic studies indicate a correct allosteric transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We and others have previously generated B10Leu mutants and shown that replacement of the ␣B10Leu residue (␣Leu-29) with phenylalanine increases the oxygen affinity and decreases the autoxidation rate of the macromolecule (6,13,15,31,32). We have also produced an octameric hemoglobin with wild type biological activities by substituting the ␣-subunit Asn-78 residue with cysteine (33). Combination of these mutations produced octameric macromolecules with unique properties that were utilized as resuscitation solutions in mice suffering traumatic brain injury combined with hemorrhagic shock.…”
Section: Hemoglobin (Hb)mentioning
confidence: 99%
“…We and others have previously generated B10Leu mutants and shown that replacement of the ␣B10Leu residue (␣Leu-29) with phenylalanine increases the oxygen affinity and decreases the autoxidation rate of the macromolecule (6,13,15,31,32). We have also produced an octameric hemoglobin with wild type biological activities by substituting the ␣-subunit Asn-78 residue with cysteine (33). Combination of these mutations produced octameric macromolecules with unique properties that were utilized as resuscitation solutions in mice suffering traumatic brain injury combined with hemorrhagic shock.…”
Section: Hemoglobin (Hb)mentioning
confidence: 99%
“…In parallel to our work, another recombinant octameric Hb has been obtained by introducing analogous substitution on the a-chains at aAsn78(EF7). This rHb aN78C also forms a stable octameric structure with a similar oxygen affinity as that of Hb A [18]. The mutation aN78C has been also associated with the aL29F or with aL29W mutation leading to an increase or decrease in oxygen affinity, respectively [38].…”
Section: Discussionmentioning
confidence: 90%
“…1) with a slightly increased oxygen affinity relative to a Hb A solution [15]. We have previously reported that this octameric rHbbG83C is resistant toward potential disulfide reducing agents present in fresh human plasma and does not interact rapidly with haptoglobin, a glycoprotein that binds Hb (ab) dimers as part of the elimination of Hb from blood circulation [15][16][17][18]. In contrast to other molecules produced by recombinant technology [19], rHbbG83 C exhibits a homogeneous size and does not dissociate into small molecular species at low concentration [15].…”
Section: Introductionmentioning
confidence: 98%